AUDIT QUALITY: INSIGHT FROM REAL AUDIT TENURE - Hariman Bone; Nurita Affan; Hamid Bone (Universitas Tidar, 2022)
This study intends to examine the association between real tenure and audit quality. There are two main reasons underlying this study: the first is the debate on the impact of tenure on audit quality between regulatory and economic perspectives. Regulatory viewpoint argues that tenure restriction could increase audit quality, while economic perspective states that such restriction could increase initial audit engagement costs instead and therefore decrease audit quality. Secondly, this study elaborates the phenomenon of pseudo auditor rotation which possibly misleads the calculation of auditor tenure in a company. This study utilizes 238 companies from various industrial sectors. The Regression test result shows positive association between real tenure and audit quality. Therefore, this result is in line with economic perspective which contradicts the restriction of audit tenure both on auditor and public accountant firms.